High temperature creep behavior of austenitic fe-ni-cr alloy - Hamzah, Esah (2013)
reep damage investigation was carried out in Fe-Ni-Cr alloy at 800°C, 900°C, and 983°C using rectangular section form of specimen. In all the tests conducted on this material, some creep curves showed primary stage, secondary stage and tertiary stage. The creep fracture shows ductile transgranular fracture where separation occurred at the dendrites carbide interface suggesting that the detrimental effect of creep was compounded by precipitation of carbides at matrix. The presence of cavities may be due to the difference in thermal expansion characteristics of the austenite and carbide during high temperature test. Coarsening of carbides lead to cavities formation within the dendrite and carbide interface and form cavities linkage due to formation of crack and finally cause creep fracture. Increase in creep temperature it will lead to increase in creep rate. The fracture modes of creep samples were investigated to predict the failure mode.